(untitled) (TAMADDUN NURI JURNALI, 2024)
This article examines the scientific and spiritual legacy of Umar Tirmizi, a scholar, commentator and sufi who occupies a special place in the history of Islamic science. It also analyzes the characteristics of the scholar’s book “Ikhlas” and its significance today.